Novel Approaches to Treating Relapsed and Refractory Multiple Myeloma with a Focus on Recent Approvals of Belantamab Mafodotin and Selinexor - Joseph NS; Tai YT; Anderson KC; Lonial S (Dove Medical Press, 2021)
Nisha S Joseph,1 Yu-Tzu Tai,2 Kenneth C Anderson,2 Sagar Lonial1 1Winship Cancer Institute, Emory University School of Medicine, Atlanta, GA, USA; 2Dana-Farber Cancer Institute, Harvard University, Boston, MA, USACorrespondence: Kenneth C AndersonDana-Farber Cancer Institute, Blood Compont, D289, 44 Binney St, Boston, MA, 02115, USATel +1 617 632-2569Email kenneth_anderson@dfci.harvard.eduAbstract: Though survival outcomes in multiple myeloma patients have improved drastically over the past few decades, there still remains an ongoing need for effective and tolerable treatment options in the relapsed and refractory space. Encouragingly, there have been three recent FDA approvals for triple-class refractory multiple myeloma, and there is promising ongoing development of additional agents with varying novel mechanisms of action. Here, we will review the most recent data on both belantamab mafodotin, an antibody drug conjugate (ADC) targeting BCMA, and selinexor, a first-in-class selective inhibitor of XPO1, as well as touch on some of the recently published data for other immunotherapies in development, namely bispecific T cell engagers, ADCs, and CAR-T cell therapies.Keywords: belantamab mafodotin, belamaf, selinexor, relapsed/refractory myeloma, myeloma